Polycystic Ovary Syndrome Markers and Mechanism - Kurniawati, Erna Yovi; Pramono, Noor; Hidayat, Syarief Thaufik; Mahati, Endang (Syifa'Medika, 2024)
Polycystic ovary syndrome (PCOS) is a complex endocrine disorder characterized by hormonal imbalances, metabolic dysregulation, and reproductive abnormalities. This study aims to elucidate the significance of PCOS markers and their mechanisms while outlining the methodology employed. A comprehensive literature review was conducted from 2020 to 2023 using databases like PubMed, ScienceDirect, EMBASE, and Google Scholar. Key search terms included "pathophysiology," "pathogenesis," "PCOS," "marker," and "biomarker," aligned with the PICOT criteria. After removing duplicates, articles underwent a two-phase screening process based on predefined inclusion criteria. Additionally, a marker mechanism flowchart was created using the Biorender application. Results highlighted the pivotal role of various markers in understanding PCOS pathophysiology and guiding clinical management. Anthropometric, visual, metabolic, inflammatory, endocrine, and oxidative stress markers were analyzed for their diagnostic, prognostic, and therapeutic implications in PCOS. The study underscores the importance of marker interactions in personalized PCOS management. Limitations in marker interpretation warrant further research to refine diagnostic accuracy and optimize therapeutic interventions. Integrating marker mechanisms enhances understanding of PCOS heterogeneity and informs targeted treatment approaches tailored to individual phenotypic variations.